1992
DOI: 10.1073/pnas.89.8.3409
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus recombinants expressing chimeric proteins of human immunodeficiency virus and gamma interferon are attenuated for nude mice.

Abstract: We have developed a method for attenuating vaccinia virus recombinants by expressing a fusion protein of a lymphokine and an immunogen. Chimeric genes were constructed that coded for y interferon (IFN-y) and structural proteins of the human immunodeficiency virus type 1 (HIV-1).In this study, we describe the biological and immunological properties of vaccinia virus recombinants expressing chimeric genes of murine or human IFN-y with glycoprotein gpl20, gag, and a fragment of gp4l. Afl fusion proteins retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 27 publications
(24 reference statements)
0
40
0
Order By: Relevance
“…The HuIFNγ gene was in- cluded to enhance safety for individuals vaccinating livestock. In our previous studies, we have shown that replication-competent VACV can be attenuated by more than a million-fold by this method (34,35,38).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The HuIFNγ gene was in- cluded to enhance safety for individuals vaccinating livestock. In our previous studies, we have shown that replication-competent VACV can be attenuated by more than a million-fold by this method (34,35,38).…”
Section: Discussionmentioning
confidence: 98%
“…Our laboratory has extensive experience in developing rVACVs for the control of a number of human and animal diseases (17,18,22,24,34,35). Multiple approaches have been used to enhance the safety of poxviruses, including deletion or insertional inactivation of genes that enhance virulence, expression of cytokines, development of replication-deficient VACVs, such as MVA and NYVAC, or host cell-restricted vectors, such as canarypox and fowlpox (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3d). As experiments in mice have demonstrated that the forced expression of IFN-c can strongly enhance VACV clearance and promote immune responses (20)(21)(22), this suggested that concomitant induction of IL-10 and/or TGF-b might limit the activity of CD8 T-cell-derived IFN-c, which would antagonize the clearance of the virus from the ovary.…”
Section: Vacv Infection In the Ovaries Induces Immune Cell Infiltratimentioning
confidence: 99%
“…In mice, these complexes have been found to enhance envelope-specific cellular and humoral immune responses [43]. In addition, several cytokines, such as IL-15 and IFN-γ, have been incorporated into anti-HIV poxvirus vaccines in an attempt to promote TH1-specific responses and induce memory [44,45].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%